IT Management Shapes Marketing Using React Native at Gold Konveksi - Yesri Elva; Sepsa Nur Rahman; Hezy Kurnia (CogITo Smart Journal, 2024)
Gold Konveksi is a small and medium-sized enterprise (SME) engaged in the garment industry that has not yet fully utilized technology in its marketing and product promotion. As a result, Gold Konveksi's market reach has been limited. This study aims to analyze the responses from questionnaires completed by respondents, with a specific focus on respondent profiles to generate brief demographic information. The objective of this study is to assess the readiness of both employees and customers of Gold Konveksi towards the adoption of new technology. The methods used in this research include data collection through questionnaires filled out by 247 respondents. The validity and reliability of the questionnaire instruments were tested using SPSS data processing. The validity test involved applying the r-value formula, compared to the r-table value, to determine validity. The reliability test was conducted using Cronbach's Alpha value compared to the reliability threshold. Additionally, the Technology Readiness Index (TRI) was calculated to measure user readiness in adopting new technology. The results of the study indicated a high level of readiness among users. The program interface was evaluated, and system testing was conducted using black box testing to ensure its functionality. Overall, the findings of the research show a high level of readiness among users in adopting new technology, which is expected to enhance transactions and sales data recording at Gold Konveksi.